Contribute to determining the quality of groundwater in Damsarkho for use it in operating a heat pump - الغدا, عُلا; جابر ديبة,; دارين برجيه , (Latakia University Journal -Engineering Sciences Series, 2024)
The burning of large quantities of fossil fuels to generate the electricity needed for heating and air-conditioning devices releases large amounts of carbon dioxide which is one of the gases that plays a major role in the greenhouse effect of our atmosphere. It is also expected that energy consumption around the world for air conditioning alone will increase 33 times by the year 2100, which threatens more fossil fuel depletion. In order to address this matter, it was necessary to follow the technology of renewable energies and most importantly, that this technology be of an acceptable cost and high economic feasibility, so that it becomes available to all. The research focuses on the hydrological study that includes the geochemistry of water with regard to its use in the heating and air conditioning circuit as a renewable and sustainable heat source. Therefore, samples were taken from 10 wells that included the parameters (bicarbonate ions, sulfate magnesium, sodium, chlorine and general hardness). It was found that the groundwater in Damsarkho is good and can be used to operate a heat pump for heating and air conditioning purposes.